Inhibitive Effect of Organic Inhibitors on the Corrosion of Mild Steel in Acidic Medium: Life Sciences-Chemistry - Singaravelu, P.; Bhadusha, N.; Dharmalingam, V (International Journal of Life Science and Pharma Research, 2022)
The aim of the present work was to study the corrosion inhibition of mild steel using organic inhibitors. The corrosion inhibition activity of a newly synthesized [4-(4-aminobenzoyl) piperazin-1-yl) (furan-2-yl) methanone (4-4-ABPFM) and [4-(4- aminophenyl) piperazin-1-yl) (furan-2-yl) methanone (4-4-APFM) was investigated on the corrosion of mild steel in 1N HCl at room temperature for two hours using different methods.Such as weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). Organic Inhibitor (4-4-ABPFM) were prepared throughout condensation of hydrochloric acid and reduction reaction using the reagent SnCl2, compound (4-4-APFM) involved a two reaction sequence of nucleophilic aromatic substitution and nitro group reduction, characterized by Fourier transform infrared spectroscopy (FT-IR). Electrochemical polarization test was also conducted to confirm the effectiveness of inhibition. Morphology of sample surfaces was respectively examined by scanning electron microscope (SEM). The result shows that the inhibition efficiency increases significantly up to 80% [4-(4-aminobenzoyl) piperazin-1-yl) (furan-2-yl) methanone (4-4-ABPFM) and 73% [4-(4-aminophenyl) piperazin-1-yl) (furan-2-yl) methanone (4-4-APFM). The optimum efficiency is obtained at (4-4-ABPFM) concentration of 100 ppm for expositing time of 2 hours at room temperature. The polarization curve shows the inhibitor behaves as a mixed inhibitor with the dominant cathodic inhibition. The adsorption of optimum concentration of both the inhibitor on the surface of mild steel in 1N HCl solution follows Langmuir adsorption isotherm. The Surface condition is improved due to the adsorption and then formation of thin layer film protection in the surface of the mild steel. The synthesized compounds show an appreciable corrosion inhibition property for mild steel in 1N HCl medium at room temperature which varies in the order: (4-4-APFM) < (4-4-ABPFM) compound.